101k views
4 votes
How would I simplify this expression

How would I simplify this expression-example-1
User JoseM
by
5.4k points

2 Answers

3 votes

Step-by-step explanation:

Let's simplify step-by-step:

9-4(3 + 4b)

Distribute:

= 9 + (-4)(3) + (-4)(4b)

= 9 + (-12) + (-16b)

Combine Like Terms:

= 9 + (-12) + (-16b)

= (-16b) +(9 + (–12) )

= -16b + (-3)

Answer:

-16b + (-3)

User Mirronelli
by
4.7k points
3 votes

Answer:

-3 - 16b

Step-by-step explanation:

by simply doing the multiplication and then add combinable terms.

9 - 4(3 + 4b) = 9 - 12 - 16b = -3 - 16b

User Didier Ghys
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.